Secularization as a sociocultural phenomenon (Journal of Philosophy Culture and Political Science, 2018)
In modern conditions of modernization, inparticular, the modernization of Kazakhstan’sThe status of religion is determined by the processessecularization, desecularization, de- and resacra-lization and religious deconstruction,dualization of religion. The above processesare indicators of the degree of religiosity,first of all, society.